Electronic Participation Fourth IFIP WG 8.5 International Conference, ePart 2012, Kristiansand, Norway, September 3-5, 2012, Proceedings - Tambouris, Efthimios.; Tambouris, Efthimios.; Macintosh, Ann.; Macintosh, Ann.; Sæbø, Øystein.; Sæbø, Øystein. (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
This book constitutes the refereed proceedings of the Fourth IFIP WG 8.5 International Conference, ePart 2012, held in Kristiansand, Norway, in September 2012. The 14 revised full papers presented were carefully reviewed and selected from numerous submissions. This volume includes complete research work organised in five groups as follows: • Keynote Speech • Reviews • Policy Consultations • Case Studies • Techniques and Analysis.